1986
DOI: 10.1128/jcm.23.5.858-862.1986
|View full text |Cite
|
Sign up to set email alerts
|

Slime production by bovine milk Staphylococcus aureus and identification of coagulase-negative staphylococcal isolates

Abstract: Staphylococcus aureus isolates from bovine milk were assessed for capsule or slime production. When pure S. aureus cultures in milk were inoculated directly into serum-soft agar constituted with a modified staphylococcus 110 medium, 100% of the isolates grew with diffuse colony morphology. Diffuse colony morphology was rapidly lost on subculture and was more rapidly lost in brain heart infusion-serum-soft agar. No evidence was seen for encapsulation in India ink preparations or by the clumping factor test. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…By comparison of the growth in SSA and India ink staining, Anderson (1) rejected the conclusions of these previous reports, claiming that strains from cases of mastitis are not encapsulated and that growth as diffuse colonies in SSA is not a reliable test of encapsulation. Recently, Rather et al (14) confirmed both the results of Norcross and Opdebeeck and those of Anderson and concluded that fresh bovine milk isolates of S. aureus produce slime, not true capsules. These authors suggested that capsule, as defined as a covering, thick polysaccharide layer outside the cell wall, demonstrable by light microscopy, occurs in very few strains.…”
mentioning
confidence: 75%
“…By comparison of the growth in SSA and India ink staining, Anderson (1) rejected the conclusions of these previous reports, claiming that strains from cases of mastitis are not encapsulated and that growth as diffuse colonies in SSA is not a reliable test of encapsulation. Recently, Rather et al (14) confirmed both the results of Norcross and Opdebeeck and those of Anderson and concluded that fresh bovine milk isolates of S. aureus produce slime, not true capsules. These authors suggested that capsule, as defined as a covering, thick polysaccharide layer outside the cell wall, demonstrable by light microscopy, occurs in very few strains.…”
mentioning
confidence: 75%
“…The negative selection for Staphylococcus aureus by culling infected cows, has resulted in more frequently isolated CNS from mastitic cases . Several reports showed that CNS could be associated with subclinical mastitis and elevated somatic cell count (SCC), ranging from 200 000 to 620 000/ml (Watts et al, 1984;Rather et al, 1986;Pyörälä and Syväjärvi, 1987;Matthews et al, 1990;Chaffer et al, 1998) or clinical mastitis (Jarp, 1991) with severe local clinical signs in the affected quarter as well as general systemic effects. Mastitis caused by CNS appears to be a disease of young cows .…”
Section: Introductionmentioning
confidence: 99%
“…Although encapsulation in S. aureus from bovine mastitis is controversial (25), recent evidence indicates that capsular polysaccharide production is a predominant feature of mastitis pathogenic S. aureus (19). The present study provides a direct demonstration of abundant capsular polysaccharide of S. aureus in situ in bovine mastitis milk.…”
Section: Discussionmentioning
confidence: 48%